PKM Kelompok Tani Tan Selo 1 dan Tan Selo 2 Desa Sukomaju Kecamatan Srono Kabupaten Banyuwangi Jawa Timur dalam Meningkatkan Nilai Ekonomis Pisang dan Strategi Pemasarannya - Nurmasari, Fitri; Padillah, Raup (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Banyuwangi Regency is one of the agricultural centers in East Java province and Indonesia. Mostly,Banyuwangi people work as farmers due to the fertil soil and wide amount of agricultural land in Banyuwangi . Thelarge number of people who work as farmers initiating the formation of farmer groups. One of the farmer groups in theSrono sub-district of Banyuwangi is the "Tan Selo 1" farmers group located in the village of Sukomaju and the "TanSelo 2" farmers group in Sukonatar village. The normal average price of one banana bunch in Banyuwangi is between50-60 thousand depending on the type and quality of bananas. Problems arise when the quantity of bananas in the marketarose, the price of 1 bunch of bananas decreases dramatically. The price of 1 bunch which is usually set at 50-60thousand drops drastically to only 20-30 thousand. This is certainly a problem for farmers in the Tan Selo group. The lackof knowledge of Tan Selo farmers about alternative variants of processed banana based products and the lack ofknowledge of the marketing strategies make it hard for the Tan Selo farmers to increase the economic value of bananaswhich have been used as an alternative income for farmers. Therefore, the solutions offered to overcome the problems offarmers include: equipping and improving farmers' knowledge about the variety of processed banana-based foods andtheir marketing strategies, conducting training to make variations on banana-based foods, conducting training oneffective marketing strategies. Overall, a series of community service programs were carried out perfectly as it expected.The percentage of participants' understanding in choosing high quality bananas is 85%, the percentage of participants?ability in processing banana-based foods is 86%, and percentage of participants who successfully sell processed foodproducts by utilizing online shopping sites is 70%